Didactic possibilities of the interactive whiteboard in development of creative thinking of young schoolchildren - Elena V. Fabrikantova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the problem of developing creative thinking of junior school-children by means of the interactive whiteboard. In his work the author defines the concept of "didactic possibilities of technical means of teaching"; concretizes the concept of "creative thinking" in relation to students of primary school age. Based on the analysis of the didactic properties of the SMART Board interactive whiteboard, the author considers the didactic possibilities of the interactive whiteboard in the teaching and educational process and correlates them with the psychophysiological characteristics of younger schoolchildren. The author notes the advantages of using an interactive whiteboard in the educational process; identifies the types of assignments aimed at developing the creative thinking of junior schoolchildren, which it is advisable to perform on an interactive whiteboard; gives as an illustration one of such tasks.